ANALISIS TINGKAT KEPUASAN KONSUMEN DENGAN MENGGUNAKAN METODE SERVICE QUALITY DAN IMPORTANCE PERFORMANCE ANALYSIS DI TOKO LAPIS LEGIT ROSALINA CAKE - Hendra Pratama; Octasena Rizqi Firdaus; Agus Ruhimat (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2025)
Lapis Legit Rosalina Cake shop is a cake shop that offers a wide variety of products such as Lapis Legit, Lapis Surabaya, Lapis Taro Bogor, Brownies, Mavin, Banana Cake, Pandan Cake, Ring Cake, Marble Cake, Tigaraksa Cake, Roll Cake, etc. Because of the diversity, many customers shop at the Lapis Legit Rosalina Cake Shop and this will have an impact on consumer loyalty. Consumer satisfaction can be achieved by providing good service quality. Good service quality can make customers feel comfortable and can make customers come back to shop again. However, from initial observations there were several complaints about customer satisfaction with the quality of services and facilities provided. This study aims to determine the level of customer satisfaction with service quality and what factors should be improved. This study took data from 65 respondents, and then performed Service Quality calculations to find out the Gap value, the Gap results were used as input data for Importance Performance Analysis (IPA) which then identified 2 attributes that must be considered in the Cartesian diagram.